Implementasi karakter peduli lingkungan di sekolah hijau - Br Ginting, Trihandayani (Universitas Tangerang Raya, 2024)
This study aims to explore how the implementation of environmental care character in high schools located in Jakarta. This research focuses on the implementation of the environmental care program. This research uses a type of qualitative research with a case study approach whose steps refer to a book with steps including, selection of topics, determining research methods and designs, determining research informants, determining data and data sources, conducting data collection procedures, analyzing and interpreting data and checking data validity, the last step is writing the results of the research that has been done. The results of the study illustrate the role of the character of environmental care by the school and all school residents who have activities in the school. Not only to school residents, guests who are present in the school are also required to apply the character of environmental care. The implementation of character culture is something that must be applied for future school development. The implementation of character gradually and sustainably balanced by regular supervision by school community will shape the character in accordance with the national education system.